Constitutionalism in Asia in the early twenty-first century - Chen, Albert H.Y. (Cambridge, United Kingdom Cambridge University Press, 2014)
"Examining developments in the first decade of the twenty-first century, this authoritative collection of essays studies the evolving practice of constitutional law and constitutionalism in Asia. It provides a comprehensive overview of the diverse constitutional issues and developments in sixteen East, Southeast and South Asian countries. It also discusses the types of constitutionalism that exist and the general trends in constitutional developments whilst offering comparative, historical and analytical perspectives on Asian constitutionalism. Written by leading scholars in the field, this book will be of great interest to students and scholars alike"
Machine generated contents note: 1. The achievement of constitutionalism in Asia: moving beyond 'constitutions without constitutionalism' Albert H. Y. Chen; 2. East Asian constitutionalism in comparative perspective Tom Ginsburg; 3. Major constitutional developments in Japan in the first decade of the twenty-first century Shojiro Sakaguchi; 4. Upgrading constitutionalism: the ups and downs of constitutional developments in South Korea since 2000 Jongcheol Kim; 5. Constitutional change in North Korea Dae-kyu Yoon; 6. Chinese constitutional dynamics: a decennial review Wang Zhenmin and Tu Kai; 7. A decade of changing constitutionalism in Taiwan: transitional and transnational perspectives Jiunn-rong Yeh and Wen-Chen Chang; 8. Hong Kong's constitutional journey: 1997-2011 Johannes Chan; 9. Constitutional developments in Vietnam in the first decade of the twenty-first century Bui Ngoc Son; 10. Constitutionalism in Burma, Cambodia and Thailand: developments in the first decade of the twenty-first century Kevin Y.L. Tan; 11. Constitutional developments in Malaysia in the first decade of the twenty-first century: a nation at the crossroads H.P. Lee; 12. 'We are feeling our way forward, step by step': the continuing Singapore experiment in the construction of communitarian constitutionalism in the twenty-first century's first decade Thio Li-ann; 13. Philippine constitutional law: majoritarian courts and elite politics Raul C. Pangalangan; 14. Promoting democracy and finding the right direction: a review of major constitutional developments in Indonesia Nadirsyah Hosen; 15. The Indian constitution in the twenty-first century: the continuing quest for empowerment, good governance and sustainability Surya Deva; 16. The old order is dying, the new order is not yet born: politics of constitution demolishing and constitution building in Nepal Yash Ghai; 17. The impact of internationalisation on national constitutions Cheryl Saunders.
Includes bibliographical references and index.
Keywords: Constitutional law -- Asia